2017
DOI: 10.1021/acsenergylett.7b00202
|View full text |Cite
|
Sign up to set email alerts
|

Thin Films and Solar Cells Based on Semiconducting Two-Dimensional Ruddlesden–Popper (CH3(CH2)3NH3)2(CH3NH3)n−1SnnI3n+1 Perovskites

Abstract: Low electrical resistivity (high dark carrier concentration) of CH 3 NH 3 SnI 3 often leads to short-circuiting in solar cells, and appropriate thin-film modifications are required to ensure functional devices. The longterm durability of organic−inorganic perovskite solar cells necessitates the protection of perovskite thin films from moisture to prevent material decomposition. Herein, we report that the electrical resistivity and the moisture stability of two-dimensional (2D) Ruddlesden−Popper (CH 3 (CH 2 ) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
255
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 368 publications
(260 citation statements)
references
References 45 publications
4
255
1
Order By: Relevance
“…[23][24][25] Unlike the comprehensive studies on lead-based perovskite, only two papers about tin-based HPSCs using lowdimensional perovskite such as (CH 3 (CH 2 ) 3 NH 3 ) 2 (CH 3 NH 3 ) n-1 Sn n I 3n+1 and PEA 2 FA n−1 Sn n I 3n+1 (n is the number of the inorganic SnI 6 octahedra layers encapsulated by the PEA + (PEA = C 6 H 5 (CH 2 ) 2 NH 3 + ) double layer, the increase (decrease) in n value means increase (decrease) in the dimension; n = ∞ 3D perovskite, n = 1 2D perovskite) were published during the preparation of this manuscript. [26,27] In both papers, the PCE of the tin-based HPSCs are still lower than 6%. Cao et al reported a PCE of 2.5% by using (CH 3 (CH 2 ) 3 NH 3 ) 2 (CH 3 NH 3 ) 3 Sn 4 I 13 (n = 4) as light harvesting layer.…”
Section: Doi: 101002/aenm201702019mentioning
confidence: 95%
See 1 more Smart Citation
“…[23][24][25] Unlike the comprehensive studies on lead-based perovskite, only two papers about tin-based HPSCs using lowdimensional perovskite such as (CH 3 (CH 2 ) 3 NH 3 ) 2 (CH 3 NH 3 ) n-1 Sn n I 3n+1 and PEA 2 FA n−1 Sn n I 3n+1 (n is the number of the inorganic SnI 6 octahedra layers encapsulated by the PEA + (PEA = C 6 H 5 (CH 2 ) 2 NH 3 + ) double layer, the increase (decrease) in n value means increase (decrease) in the dimension; n = ∞ 3D perovskite, n = 1 2D perovskite) were published during the preparation of this manuscript. [26,27] In both papers, the PCE of the tin-based HPSCs are still lower than 6%. Cao et al reported a PCE of 2.5% by using (CH 3 (CH 2 ) 3 NH 3 ) 2 (CH 3 NH 3 ) 3 Sn 4 I 13 (n = 4) as light harvesting layer.…”
Section: Doi: 101002/aenm201702019mentioning
confidence: 95%
“…Cao et al reported a PCE of 2.5% by using (CH 3 (CH 2 ) 3 NH 3 ) 2 (CH 3 NH 3 ) 3 Sn 4 I 13 (n = 4) as light harvesting layer. [26] Ning and co-workers reported a PCE of 5.9% using PEA 2 FA 8 Sn 9 I 28 (n = 9) as light harvesting layer. [27] For the low-dimensional tin-based perovskite family (CH 3 (CH 2 ) 3 NH 3 ) 2 (CH 3 NH 3 ) n-1 Sn n I 3n+1 and PEA 2 FA n−1 Sn n I 3n+1 , how the device using tin perovskite with lower content of bulkier organic cations (∞ >n > 5 for CH 3 (CH 2 ) 3 NH 3 ) 2 (CH 3 N H 3 ) n−1 Sn n I 3n+1 , ∞ > n > 9 for PEA 2 FA n−1 Sn n I 3n+1 ) as light harvesting layer behaves, remains an open question.…”
Section: Doi: 101002/aenm201702019mentioning
confidence: 99%
“…A series of 2D (CH 3 (CH 2 ) 3 NH 3 ) 2 (CH 3 NH 3 ) n −1 Sn n I 3 n +1 perovskites was recently introduced as stable and promising alternatives of 3D ASnX 3 HPs for photovoltaic applications [75]. The 2D HPs revealed semiconductor properties with a bandgap decreasing from 1.83 eV for n = 1 to 1.2 eV at n → ∞ (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…The Sn 4 I 13 “isomer” with a “close-to-ideal” E g of 1.42 eV was suggested as an optimal light harvester, displaying a promising PCE of 2.5% (Table 1) [75]. …”
Section: Reviewmentioning
confidence: 99%
“…Recent breakthrough in the synthesis of phase-pure (a single n -value) RPPs with higher values 35 of n , up to n equals to 5, has inspired their use as low-cost semiconductors in optoelectronics 58 as an alternative to three-dimensional (3D) perovskites due to their technologically relevant intrinsic photo- and chemical-stability 510 . However, key fundamental questions remain unanswered in RPPs with n greater than 1, such as the nature of optical transitions, as well as the behavior of Coulomb interactions especially with increasing quantum well thickness.…”
Section: Introductionmentioning
confidence: 99%